FACTORS INFLUENCING MISUSE OF ANTIBIOTIC THERAPY IN AL-QASSIM REGION, SAUDI ARABIA: Pharmaceutical Science-Medicine - NEGIKHAN OTAIBI, NAIF; ALMUTAIRI, MAJED; ZAID AL-NAMSHAN, YOUSSEF; ABDULRAHMAN AL DHOHAYAN, MOHAMMAD; DEEB ALOTIBI, RAKAN (International Journal of Life Science and Pharma Research, 2019)
Globally, about 66% of oral antibiotics are taken without prescription with an aim to treat diseases which are mostly viral or protozoal in origin such as malaria, flu and pneumonia. In the developing countries, recent developments in healthcare and improvement in income have increased the use of antibiotics. This study is aimed to assess the pattern of antibiotic misuse in Al-Qassim region and factors associated with this misuse. This is a cross sectional community-based study. About 596 study participants selected and recruited randomly from localities of Al-Qassim region in Saudi Arabia. After obtaining written consents, the data were gathered using questionnaires which consisted of two parts namely Part1 for demographic variables and part B for data about behaviors in antibiotic use. The descriptive statistics were obtained for the distribution and patterns of antibiotic misuse. To adjust for confounding effect, a multiple logistic regression was performed. Thus, demographic variables were introduced to the model as predictors and the use of prescribed antibiotics as a dependent variable. Approximately one third of the respondents used antibiotics without doctors’ prescriptions, while pharmacists were consulted in the 11% of the respondents. About 19% of the respondents practiced self-medications. Age, income and the PhD level of education were found to be significantly predicting the possibility of taking antibiotics with prescriptions. Those who aged 30 years old or more were 1.76. They were more likely to use antibiotics with doctor’s prescription than those who aged <30 years old. The respondent with low income were more likely to take antibiotics based on the medical prescriptions. We concluded that a prevalence of antibiotics misuse is high in Al-Qassim region but the compliance with drug instructions are generally good.